Eco-print Exploration As An Effort To Improve Writing Ability Based On Project Based Learning (Pjbl) - Yusro, Indah Setyaning Usri; Yonatin, Vury Putri; Rochmiyati, Siti; Susanto, Moh Rusnoto; Arumsari, Mela Dina (V-art: Journal of Fine Art, 2024)
The low ability to write procedure texts for making eco-prints for students in grades V and VI is caused by several things that must be observed. This is due to students' lack of understanding of procedural texts, difficulty communicating knowledge in written form, and difficulty composing effective sentences. This research aims to analyze Eco-print exploration activities as an effort to improve writing skills based on project-based learning (PjBL) integrated with Tri-N (niteni, niroake, nambahi). Tri-N concert encourages students to have the ability to observe and scrutinize an object or the stages of the Eco-print process. Then, imitate with a bank that will eventually grow creativity and innovation.  This research uses the narrative method to describe the steps of making eco-print, which serves as teaching material to improve students' writing skills. The data collection technique in this research is using observation, interview and documentation techniques. The research findings show that Eco-print exploration activities with the stages of the work creation process are able to explore, narrate the stages, and ultimately foster the ability to write a narrative based on project-based learning (PjBL) integrated with Tri-N (niteni, niroake, nambahi). Through the narrative approach, it can improve students' writing skills, especially in terms of writing descriptions and creativity. The implications of this study highlight the potential of using hands-on activities, such as eco-print making, to improve students' writing skills and enhance their understanding of the writing process.